Voice Controlled Smart Mirror with Raspberry PI - Prof. Sampada H K,Nihal B S,Charan C,Karthik G S, Kankshita S Gunasheela B.G (International Journal of Advanced Science and Technology, 2020)
Observation has been made that the time spent by the individuals before the mirror cannot be informative and an extra time is spent to pick up this information, for example, news, climate estimate, and email, personal and public calendar and so on. To tackle the above issue, we proposed "Smart Mirror" as an answer. Smart Mirror deals with the Internet of Things (IoT) innovation. IoT is the bury association of a few physical gadgets to the web, empowering them to send and get information. We will build a Smart mirror gadget that fills in as a normal mirror, yet additionally has the capacities to show logical data like climate estimate, news source, time, personal and public calendar etc. The primary idea for this gadget is Raspberry Pi. In our model we are utilizing Raspberry Pi 3B+. To make our gadget intelligent we are utilizing "ALEXA" as our voice services. "ALEXA" will have the option to respond to client’s interested enquiries.